Allometry of mangrove horseshoe crab, Carcinoscorpius rotundicauda along Peninsular Malaysia coastal waters - Isa, Nor Syuhaida; Mohamed, Rozihan; B., Akbar John; Sobari, Mohd Akmal; Darmansuri, Joni Haryandi; Esa, Yuzine (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Carcinoscorpious rotundicauda is mangrove horseshoe crab that inhabit in mudflats ecosystem. The values information on morphometric variability of C. rotundicauda is still limited especially along coastal of Peninsular Malaysia. In this study, the allometric relationship will be applied to make comparison on morphometric parameters of male and female of C. rotundicauda with different ages and population. A total of 158 samples of C. rotundicauda were collected randomly from Merlimau, Melaka and Pantai Balok, Pahang characterized by different environmental conditions in order to study the intraspecific variations using allometry relationship. Body weight for male C. rotundicauda was 88.02±21.71 g and female was 103.12±33.04 g in Merlimau while in Pantai Balok, the mean for body weight in male was 123.23±31.52 g and female was 177.05±70.98 g. All morphometric parameter were converted into logarithmic value as allometric growth analysis. A negative allometric growth (b<3) was recorded for relationship of length/weight- total length analysis in both population. Overall performance showed that increment of all body parts of female C. rotundicauda showed better growth than males. Follow up study on the relationship of horseshoe crab population growth are needed in developing strategies on monitoring, conservation and breeding of horseshoe crab.